Pika’s role in the Qinghai-Tibet Plateau ecosystem and effects of biodiversity - Hong Zimu; Jiang Xiaoyu; Li Rourou (BIO Web of Conferences)
The Tibetan Plateau is the largest plateau in the world. Although this plateau is not as rich in species as the rainforest, it still contains some specific flora and fauna (including mammals, birds, and some reptiles). These special organisms make up biodiversity. It refers to the sum total of genes, species and ecosystems within a given area. Biodiversity produces a variety of direct and indirect benefits. These benefits are significant for human health and well-being. On the Tibetan Plateau lives a small mammal called the pika. Pika plays an important role in the plateau ecosystem and has an impact on biodiversity. However, despite the vital role pikas play in the ecosystem, the government considers them to be responsible for the degradation of grasslands and vegetation, and kills them to restore pastures. Some advocates and scholars have made different arguments based on this situation. They believe the pika also protected the plateau ecosystem, rather than damaging the grasslands. There was no direct relationship between grassland degradation and pika. In addition, a decline in the pika population would also lead to a decline in other carnivores. These wild animals may choose to attack poultry and livestock. Conflicts between humans and animals will intensify. If China wants to implement a biodiversity protection policy on the Qinghai-Tibet Plateau. They should observe and acknowledge that pikas play a vital role in the plateau ecosystem and stop killing them. This paper describes the characteristics, habitat, population, reproduction, behavior, plateau adaptation, role in ecosystem and impact on biodiversity of pika.